SISTEM PELAYANAN DAN MANFAAT BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN DI KELURAHAN KULIM KECAMATAN KULIM KOTA PEKANBARU - Firdaus , Muhammad; Monicha, Cindy; Padilla, Raihan safa; Annisa, Aulia (Awal Bros Journal of Community Development, 2022)
The Social Security implementation agency is a legal entity to administer social security programs to ensure that all people can meet the basic needs of a decent life. Based on the Law of the Republic of Indonesia Number 24 of 2011 concerning The Social Security implementation agency , it is stated that "Everyone, including foreigners who work for a minimum of 6 (six) months in Indonesia, is obliged to become a Participant of the Social Security program". There are still many people in Kulim Village who do not use The Social Security implementation agency Health because they do not know how The Social Security implementation agency health service system is and the benefits of The Social Security implementation agency Health are caused by a lack of knowledge and counseling about The Social Security implementation agency Health. The socialization activity was carried out in Kulim Village at the al-istiqomah mosque RW02. This activity aims to increase public knowledge so that they understand how The Social Security implementation agency Health service system is and what are the benefits of Social Security implementation agency Health and can use it as needed. The method used is lectures and discussion questions and answers by the community and resource persons.